Mood fluctuations and seasonal affective disorder : are there daily fluctuations of positive and negative mood in individuals at risk of seasonal affective disorder? - Silja Rún Friðriksdóttir 2000- (2024)
Seasonal Affective Disorder is a prevalent mental health condition that significantly impacts individuals daily functioning and well-being. Despite its prevalence, there remains a need for a deeper understanding of the underlying mechanisms and effective interventions. This study utilizes data collected form the EPiC SAD study conducted at the University of Akureyri to explore mood fluctuations throughout the day in individuals with varying levels of seasonality, aiming to uncover potential associations between mood changes and rumination tendencies in those at high risk for SAD. Utilizing the Seasonal Pattern Assessment Questionnaire (SPAQ) and the Experienced Sampling Method (ESM), data were collected from N=118 participants categorized into high (N=62) and low (N=56) seasonality groups. Results indicate no significant differences in mood fluctuations between the groups or in the association between mood changes and rumination tendencies. This study is not in line with previous work, and the explanations could be a relatively small sample size and potential participant responsiveness bias in ESM research. The study still found evidence that it is important to have a larger sample size to increase the statistical power of a study, and the participants responsiveness can influence the validity of the results, so it is essential to consider and possibly control for this factor in future research. Overall, this research contributes to the understanding of mood fluctuations and rumination in individuals at risk for SAD, providing insights for further investigation and possible treatments aimed at improving mental health outcomes. Árstíðabundin tilfinningaröskun er algeng röskun sem getur haft mikil áhrif á daglegt líf og líðan þeirra sem við hana glíma. Þrátt fyrir algengi hennar vantar ennþá upp á dýpri skilning á árstíðabundinni tilfinningaröskun, því sem liggur henni að baki, og mögulegum meðferðum. Þessi rannsókn notast við gögn frá EPiC SAD rannsókn á vegum Háskólanns á Akureyri þar sem skoðaðar eru ...